2015
DOI: 10.1182/blood-2014-04-570960
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Janus-faced transcription factor PAX5-JAK2 in acute lymphoblastic leukemia

Abstract: Key Points• PAX5-JAK2 is the first nuclear DNA-binding JAK2 fusion protein with kinase activity.• JAK2 inhibitors block the kinase activity of PAX5-JAK2.PAX5-JAK2 has recently been identified as a novel recurrent fusion gene in B-cell precursor acute lymphoblastic leukemia, but the function of the encoded chimeric proteinhas not yet been characterized in detail. Herein we show that the PAX5-JAK2 chimera, which consists of the DNA-binding paired domain of PAX5 and the active kinase domain of JAK2, is a nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 75 publications
5
62
0
1
Order By: Relevance
“…Kinase fusions and sequence mutations confer cytokine-independent proliferation in mouse pre-B-cell lines that is abrogated by tyrosine kinase inhibitors (TKIs), ABL1 inhibitors such as imatinib and dasatinib for ABL-class fusions, and JAK2 inhibitors for JAK-STAT-activating alterations. 14,22,53 Human Ph-like leukemic cells show similar pathway activation and sensitivity to TKI in vitro and in xenograft models. There are several reports of Ph-like ALL with ABL-class rearrangements poorly responsive to chemotherapy with profound TKI responses, 22,54 which have led to prospective precision medicine trials of TKI therapy in Ph-like ALL.…”
mentioning
confidence: 99%
“…Kinase fusions and sequence mutations confer cytokine-independent proliferation in mouse pre-B-cell lines that is abrogated by tyrosine kinase inhibitors (TKIs), ABL1 inhibitors such as imatinib and dasatinib for ABL-class fusions, and JAK2 inhibitors for JAK-STAT-activating alterations. 14,22,53 Human Ph-like leukemic cells show similar pathway activation and sensitivity to TKI in vitro and in xenograft models. There are several reports of Ph-like ALL with ABL-class rearrangements poorly responsive to chemotherapy with profound TKI responses, 22,54 which have led to prospective precision medicine trials of TKI therapy in Ph-like ALL.…”
mentioning
confidence: 99%
“…The most commonly used approach to TKI sensitivity testing is based on exploitation of the murine Ba/F3 cell line carrying mutant BCR-ABL1 constructs introduced by LV-mediated transduction [20]. Here we present an alternative technique, the transposon-based SB system, which offers advantages with regard to efficacy, speed, and safety [32-34, 40]. Nevertheless, we have demonstrated that both technical approaches can lead to multiple insertions of BCR-ABL1 gene constructs which result in artificially elevated IC 50 values for the TKIs tested.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to lentiviruses, there is no preference for coding or non-coding regions [30]. The SB system is a fast, simple and safe procedure for stable gene transfer facilitating efficient transfection even of large constructs [31-34]. However, similar to LV transduction, the SB system is also prone to generating multiple insertions in the genome which may be favored during the selection of engineered cells in culture [30, 35].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of JAK2 inhibitors, such as ruxolitinib or AZD1480, with BH3-mimetics enhanced the limited efficacy of JAK inhibitors as single agents (60,61). Waibel et al (62) used an E-TEL-JAK2 (ETV6-JAK2) mouse model of T-ALL to show that up-regulation of BCL-2/BCL-X L and down-regulation of BIM expression promote leukemic cell survival.…”
Section: Jak2 Fusions and The Role Of Bcl-x Lmentioning
confidence: 99%